2003
DOI: 10.1080/1355621031000069873
|View full text |Cite
|
Sign up to set email alerts
|

User views on supervised methadone consumption

Abstract: To assess the views of opiate-dependent individuals about supervised methadone consumption. Three groups of opinions were sought: (i). new patients referred for assessment and treatment, using rating scales; (ii). the consensus view of the Methadone Alliance (a national users' forum); and (iii). the consensus view of a local service users' forum. All three groups expressed the view that supervised consumption has an important place in methadone treatments. Users understand the need for daily supervision of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…An existing UK study of supervision had already suggested that the possibility of moving away from supervision might be important for patients [12]. However, this study collected patients' views prior to entering treatment, and thus did not assess actual treatment experiences.…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…An existing UK study of supervision had already suggested that the possibility of moving away from supervision might be important for patients [12]. However, this study collected patients' views prior to entering treatment, and thus did not assess actual treatment experiences.…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 96%
“…It was suggested that there should be adequate privacy for supervised consumption services [11]. A UK study identified that patients understood the need for supervised consumption but considered privacy within pharmacies and the possibility of moving away from supervision to be important [12]. A further study also found a generally positive response to supervision and agreement that supervision reduced the amount of street methadone [13].…”
Section: Introductionmentioning
confidence: 94%
“…Participants gave less favourable ratings of the privacy afforded during supervised dosing, which may reflect that many pharmacies do not have a private, separate area in the pharmacy for administering methadone and buprenorphine, often due to space limitations. The issue of privacy has been cited as an issue of concern by both clients and other customers of the pharmacy [11][12][13]20]. However, some pharmacists cite that wherever possible they try to dose clients discreetly, at less busy times, or when other customers are not in the pharmacy [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the treatment experiences of community pharmacy clients have received some attention. Studies in the UK and Australia have explored client perceptions of treatment and issues relating to staff attitudes, privacy during supervised dosing, flexibility regarding takeaway dosing, the cost of treatment and being treated differently from other customers [3,[9][10][11][12][13]. A recent study of 432 clients receiving methadone and buprenorphine treatment at public clinics in NSW found that while clients were generally satisfied with treatment, they were dissatisfied with the frequency of clinic attendance for dosing, inflexible dosing hours, and a lack of takeaway doses [14].…”
Section: Introductionmentioning
confidence: 99%
“…Retention in treatment is similar (Fiellin et al, 2006;Bell et al, 2007;Moore et al, 2012) or even improved (Holland et al, 2012) in comparison with observed dosing. OST patients value unobserved dosing and consider it as an essential part of OST (Stone & Fletcher, 2003;Treloar, Fraser, & Valentine, 2007;Madden, Lea, Bath, & Winstock, 2008).…”
Section: Introductionmentioning
confidence: 99%